Romania : Second and Third Reviews under the Stand-By Arrangement, Request Rephasing and Waiver of Nonobservance of Performance Criterion; Statement by the IMF Staff Representative; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Second and Third Reviews under the Stand-By Arrangement for Romania. Most end-December 2009 quantitative performance criteria were met. The ceiling on the accumulation of domestic arrears at end-September was missed, and preliminary data suggest the end-December target was also missed. The end-2009 inflation rate was slightly higher than the central bank target, but remained well within the inner band of the inflation consultation mechanism. The authorities have agreed to reschedule the benchmark for end-June 2010. IMF staff supports the waiver requested by the authorities.